ANÁLISIS Y EVALUACIÓN DEL RIESGO DE CRÉDITO EN LA COOPERATIVA DE AHORRO Y CRÉDITO QUILANGA LTDA., PERIODO 2016-2017 - Yaguana Abad., Dalila Elizabeth (2019)
The present thesis work called. "ANALYSIS AND EVALUATION OF CREDIT RISK IN THE QUILANGA LTDA. SAVINGS AND CREDIT COOPERATIVE, PERIOD 2016-2017", was developed with the purpose of performing an analysis to determine the growth or decrease of the credit portfolio, as well as the application of indicators that allowed identifying the possible credit risks, and making the final report, fulfilling the objectives set out in the research work. In order to comply with the first specific objective, an analysis of growth and decrease of the credit portfolio period 2016-2017 was carried out, making it possible to determine the current situation in each year, knowing what the factors have been that have contributed to it. increases and decreases, specifying that the loan portfolio had a large increase in each year analyzed. In the application of the indicators, those that are pertinent to credit were applied, which helped to propose strategies to facilitate the recovery of the past due portfolio, avoiding credit risks. Finally, the final report was made with qualitative and quantitative elements on the management and administration of the credit portfolio through conclusions and recommendations.